Penguatan Literasi Numerasi Melalui Aktivitas Membaca, Menulis, Dan Berhitung Di SMP Negeri 44 Bandar Lampung - Erizal Barnawi; Afifah Oktaviani; Riska Meilisa; Silvi Desta Ariani; Natasya Distianuari; Masbekti Luhur Pekerti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to describe efforts to strengthen literacy and numeracy through reading, writing, and counting activities at SMP Negeri 44 Bandar Lampung. The background of this study is based on the importance of improving students’ literacy and numeracy skills as a foundation for facing the challenges of 21st-century learning. The method employed was a descriptive qualitative approach, with data collected through observation and documentation. The activities implemented included reading habituation, structured writing exercises, and contextual counting activities integrated into the learning process. The findings indicate that the consistent implementation of reading, writing, and counting activities enhances students’ reading comprehension, written expression skills, as well as logical thinking and mathematical problem-solving abilities. Therefore, strengthening literacy and numeracy through simple yet structured activities can serve as an effective strategy to improve the quality of learning in schools.